A Novel Approach for the Management and Prevention of Self-Induced Masticatory Lingual Trauma in the Neurologically Injured Patient. Issue 3 (September 2018) - Avashia, Yash; Bittar, Peter; Suresh, Visakha; Powers, David B.
Self-induced masticatory trauma is an unfortunate complication of a variety of neurologic disorders, including epileptic seizures, cerebral palsy, mental retardation, psychiatric disease, and brain trauma, in addition to other described etiologies. While single or occasional occurrences of tongue biting are relatively benign, recurrent self-injury can pose major issues and predispose a patient to chronic, severe complications. To prevent the complications associated with ongoing trauma to the tongue, steps must be taken to protect individuals from chronic self-injurious behavior. Often, these interventions cause significant morbidity to the patient, such as elective removal of the dentition or complications in gaining access to the oral cavity/airway associated with maxillomandibular fixation. In the neurologically impaired patient, immobilization of the jaws is frequently associated with higher rates of agitation, aspiration, or development of complicating infections of the gingival tissues. We report a case of self-induced masticatory trauma managed with the fabrication of a custom-fabricated oral appliance. This treatment modality successfully prevents the recurrence or incidence of self-induced masticatory trauma to the tongue. The benefits of this modality are that it allows access to the oral cavity, prevents immobilization of the jaws, has minimal to no morbidity, and is completely reversible.